Status of common disease profile and death records among admitted child patients in medical college hospital - Shahariar Khan, Md.; Rahimullah Miah, Md.; Hussain, Tania; Moosa M.A. Quaium, Syed; Rahman, Azizur (International Journal of Health, 2020)
Background: The study assesses the common disease profile and death records among admitted child patients at the department of Paediatrics in Northeast Medical College Hospital (NEMCH) of Bangladesh.Methodology: This was an observational study conducted in the department of Paediatrics in Medical College Hospital over a period of three years. The patients of common diseases were hundred in number surveyed through primary questionnaire in respect to their profile, diagnosis and death records. The selected common diseases were ARI, diarrhoea, protein energy malnutrition and febrile convulsion.Results: The numbers of total admitted child patients with common diseases were 10737 for three years with the ratio of 1: 0.93 between the male and female. Out of them neonatal and general patients were 3622 and 7115 respectively. In 2018 child patients were less in numbers other than two years. ARI is more common in the end of year but diarrhoea in same added the beginning of following year. The study also represents the febrile convulsion and malnutrition are more in middle and round the year successively.From 2017 to 2019 the death records of neonate and general at the department of NEMCH are 101 and 84 respectively. Indeed, it is a good sign to reducing the unwanted death in common disease through the consecutive year. A systematic control model is developed to recover from the common diseases associated with hospital admitted child patientsâ€™ management.Conclusion: If the medical authority can take advances in preventive measures through health awareness, quality training, safe health care with equipment, facilities and trained-up personnel, then the mortality and morbidity can be reduced suggestively in connection with dynamic National Health Policy and Sustainable Development Goals 2030.Â Â